2019
DOI: 10.1016/j.ijrobp.2019.06.539
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Re-Irradiation and Concurrent Bevacizumab versus Bevacizumab Alone as Treatment for Recurrent Glioblastoma (NRG Oncology/RTOG 1205): Initial Outcomes and RT Plan Quality Report

Abstract: HFRT should be limited to small volume recurrences especially in previously non-irradiated treatment areas at least 6 months following completion of previous RT. Due to treatment plan complexity, future re-irradiation GBM trials should require real time RT review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 0 publications
1
39
0
2
Order By: Relevance
“… 19 The role of bevacizumab with RT remains to be determined, and preliminary results from the prospective Radiation Therapy Oncology Group trial 1205 indicate that the addition of hypofractionated RT to bevacizumab improves PFS, but not OS. 20 …”
Section: Discussionmentioning
confidence: 99%
“… 19 The role of bevacizumab with RT remains to be determined, and preliminary results from the prospective Radiation Therapy Oncology Group trial 1205 indicate that the addition of hypofractionated RT to bevacizumab improves PFS, but not OS. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Survival benefits have been reported following fractionated SRT and concurrent bevacizumab [ 12 , 55 , 60 , 64 68 ]. Gutin et al [ 55 ] observed a median overall survival time of 12.5 months and 1-year survival rate of 54% in twenty patients who received 30 Gy in 5 fractions to the recurrent tumor with SRT; median progression-free survival time and 6-month rates were 7.4 months and 65%, respectively.…”
Section: Survival Outcomes and Toxicitymentioning
confidence: 99%
“…In a small retrospective study comparing hypofractionated SRT (25 Gy in 5-Gy fractions) plus bevacizumab or the alkylating agent fotemustine, median survival times and 12-month survival rates were 11 months and 30% for patients treated with SRT and bevacizumab and 8.3 months and 5% for those treated with SRT and fotemustine (p = 0.01); respective median progression-free survival times were 6 and 4 months (p = 0.01). In a recent multi-institutional, prospective randomized phase II trial (NRG Oncology/Radiation Therapy Oncology Group (RTOG) trial 1205) designed to evaluate the safety and efficacy of reirradiation for recurrent GBM with modern radiation techniques, a similar survival of 10.1 months has been observed following hypofractionated SRT (35 Gy/10 fractions) and concurrent bevacizumab [ 68 ].…”
Section: Survival Outcomes and Toxicitymentioning
confidence: 99%
“…Thus, the survival in this prospective trial compares favorably to those series. Moreover, the one prospective trial of reirradiation in recurrent GBM for bevacizumab-naïve patients, Radiation Therapy Oncology Group (RTOG) 1205, failed to show an incremental benefit of radiation given via 35 Gy in 10 fractions when added to bevacizumab in this population [30].…”
Section: Discussionmentioning
confidence: 99%